Cloud-based BP system integrated with CPOE improves self-management of the hypertensive patients: A randomized controlled trial. Issue 132 (August 2016) - Lee, Peisan; Liu, Ju-Chi; Hsieh, Ming-Hsiung; Hao, Wen-Rui; Tseng, Yuan-Teng; Liu, Shuen-Hsin; Lin, Yung-Kuo; Sung, Li-Chin; Huang, Jen-Hung; Yang, Hung-Yu; Ye, Jong-Shiuan; Zheng, He-Shun; et al.
Highlights: Cloud-based BP system integrated with CPOE at the point of care achieved better BP control compared to traditional care. Cloud BP records positively reinforced both BP measuring and medication adherence behaviors. Cloud-based BP system does not require any technical skills and is therefore suitable for every age group. Abstract: Background: Less than 50% of patients with hypertensive disease manage to maintain their blood pressure (BP) within normal levels. Objective: The aim of this study is to evaluate whether cloud BP system integrated with computerized physician order entry (CPOE) can improve BP management as compared with traditional care. Methods: A randomized controlled trial done on a random sample of 382 adults recruited from 786 patients who had been diagnosed with hypertension and receiving treatment for hypertension in two district hospitals in the north of Taiwan. Physicians had access to cloud BP data from CPOE. Neither patients nor physicians were blinded to group assignment. The study was conducted over a period of seven months. Results: At baseline, the enrollees were 50% male with a mean (SD) age of 58.18 (10.83) years. The mean sitting BP of both arms was no different. The proportion of patients with BP control at two, four and six months was significantly greater in the intervention group than in the control group. The average capture rates of blood pressure in the intervention group were also significantly higher than the control group in all three check-points. Conclusions: Cloud-based BP system integrated with CPOE at the point of care achieved better BP control compared to traditional care. This system does not require any technical skills and is therefore suitable for every age group. The praise and assurance to the patients from the physicians after reviewing the Cloud BP records positively reinforced both BP measuring and medication adherence behaviors.